Investigation on the effect of natural kaolin substitution on geopolymer mortar made by a combination of fly ash and rice husk ash - Wardhono, Arie; Sofianto, Mochamad Firmansyah; Wulandari, Meity (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate the potential of using natural kaolin (NKL) as a substitute for rice husk ash (RHA) in fly ash-rice husk ash-based geopolymer mortar (FARH-GM) applications as eco-friendly materials. The effect of NKL substitution was investigated by compressive strength, porosity, and depth penetration tests at 1%, 2%, and 3% of the composition in FARH-GM. The chemical compound analysis was identified using XRF and XRD techniques. The results showed that the 2% NKL substitution for RHA demonstrates the highest compressive strength and the lowest porosity value of FARH-GM, with a final setting time of 3.5 hours. However, increasing the NKL substitution ratio by more than 2% significantly decreases the strength performance and tends to prolong the setting time. The substitution of NKL also considerably affects the Si/Al and Si/Fe ratios, which increase along with the increase of NKL. The highest strength was achieved with Si/Al and Si/Fe ratios of 4.59 and 1.71, respectively. Furthermore, higher NKL substitution tends to increase the crystalline peak, indicating the presence of albite, anorthite, and cristobalite crystalline phases. These results suggest that natural kaolin can be used as a substitute in geopolymer applications at a specific ratio.